Ewing’s sarcoma of the head and neck - Fonseca, Adriano Santana; Mezzalira, Raquel; Crespo, Agrício Nubiato; Bortoleto Junior, Antônio Emílio; Paschoal, Jorge Rizzato (São Paulo Medical Journal, 2000)
CONTEXT: Ewing’s sarcoma is a rare neoplasm, which usually arises in long bones of the limbs and in flat bones of the pelvis, with the involvement of head and neck bones being very unusual. CASE REPORT: a case of Ewing’s sarcoma occurring in the mandible of a 35-year-old female. Pain and swelling of the tumor were the main complaints. The early hypothesis was an undifferentiated malignant neoplasm, possibly a sarcoma. The CT scan depicted an expansive lesion, encapsulated, with septa and characteristics of soft tissue, involving the left side of the mandible and extending to the surrounding tissues. The patient underwent surgical excision of the lesion, the definitive diagnosis of Ewing’s sarcoma was established, and the patient commenced on radiotherapy.